2012
DOI: 10.1016/j.neurobiolaging.2011.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in circadian rhythmicity and sleep homeostasis in older people: effect of a PER3 polymorphism

Abstract: Aging is associated with marked changes in the timing, consolidation and structure of sleep. Older people wake up frequently, get up earlier and have less slow wave sleep than young people, although the extent of these age-related changes differs considerably between individuals. Interindividual differences in homeostatic sleep regulation in young volunteers are associated with the variable-number, tandem-repeat (VNTR) polymorphism (rs57875989) in the coding region of the circadian clock gene PERIOD3 (PER3). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 40 publications
1
44
1
Order By: Relevance
“…genotypes, although a recent study in older people does report a phase advance in melatonin in PER3 5/5 subjects compared to PER 4/4 (Viola et al, 2011). The influence of the PER3 VNTR on CT appears to be more closely linked with mechanisms that regulate sleep timing and homeostasis.…”
Section: Genetic Basismentioning
confidence: 84%
“…genotypes, although a recent study in older people does report a phase advance in melatonin in PER3 5/5 subjects compared to PER 4/4 (Viola et al, 2011). The influence of the PER3 VNTR on CT appears to be more closely linked with mechanisms that regulate sleep timing and homeostasis.…”
Section: Genetic Basismentioning
confidence: 84%
“…At the gene level, polymorphisms and mutations in clock genes correlate with variation in sleep timing and duration [50,51,52] and sleep structure [53,54,55]. Individual differences in the timing of molecular rhythms and melatonin concentrations in blood also correlate with individual differences in sleep timing [56].…”
Section: Sleep As a Circadian Adaptive Rhythmmentioning
confidence: 99%
“…We found a similar trend in Canada, as older adults, relative to younger ones, had significantly increased likelihood of having troubled sleep. Epidemiological studies have shown that older adults have less slow-wave sleep (deep sleep) and rapid eye movement sleep, which affects their quality of sleep compared to those in their youthful years [63,64]. This may account for the differences seen between the older and the younger generation.…”
Section: Tablementioning
confidence: 99%